Changes in Continuous, Long-Term Heart Rate Variability and Individualized Physiological Responses to Wellness and Vacation Interventions Using a Wearable Sensor - Pratap, Abhishek; Steinhubl, Steve; Neto, Elias Chaibub; Wegerich, Stephan W.; Peterson, Christine Tara; Weiss, Lizzy; Patel, Sheila; Chopra, Deepak; Mills, Paul J. (Frontiers in Cardiovascular Medicine, 2020)
There are many approaches to maintaining wellness, including taking a simple vacation to attending highly structured wellness retreats, which typically regulate the attendee’s personal time and activities. In a healthy English-speaking cohort of 112 women and men (aged 30-80 years), this study examined the effects of participating in either a 6-day intensive wellness retreat based on Ayurvedic medicine principles or unstructured 6-day vacation at the same wellness center setting. Heart rate variability (HRV) was monitored continuously using a wearable ECG sensor patch for up to 7 days prior to, during, and one-month following participation in the interventions. Additionally, salivary cortisol levels were assessed for all participants at multiple times during the day. Continual HRV monitoring data in the real-world setting was seen to be associated with demographic (HRVALF:βAge =0.98[CI=0.96-0.98], FDR < .001) and physiological characteristics (HRVPLF:β=0.98[CI=0.98-1], FDR=.005) of participants. HRV features were also able to quantify known diurnal variations ( HRVLF/HF:βACT:night vs early-morning=2.69[SE=1.26], FDR < .001) along with notable inter- and intra- person heterogeneity in response to intervention. A statistically significant increase in HRVALF (β = 1.48 [SE=1.1], FDR < .001 ) was observed for all participants during the resort visit. Personalized HRV analysis at an individual level showed a distinct individualized response to intervention, further supporting the utility of using continuous real-world tracking of HRV at an individual level to objectively measure responses to potentially stressful or relaxing settings.